CMET-22. INTRATHECAL (IT) TRAZTUZUMAB (T) FOR THE TREATMENT OF LEPTOMENINGEAL METASTASES (LM) IN PATIENTS (PTS) WITH HUMAN EPIDERMAL GROWTH FACTOR RECEPTOR 2-POSITIVE (HER2+) CANCER: A MULTICENTER PHASE 1/2 STUDY. (5th November 2018) - Kumthekar, Priya; Gradishar, William; Lin, Nancy; Pentsova, Elena; Groves, Morris; Jeyapalan, Suriya; Melisko, Michelle; Grimm, Sean; B. Lassman, Andrew; Raizer, Jeffrey
Abstract: Pts with HER2+ breast cancer have frequent LM. No current FDA approvals exist. A multicenter phase I/II trial assessing safety and efficacy of IT T in LM pts was conducted. The primary endpoint in phase 2 was response rate (RR). Complete response (CR) required cytologic CR (CCR) + radiographic CR (RCR) + stable clinical function. Partial response (PR) required either CCR with stable/improved imaging and clinical function or RCR + stable cytology + stable/improving clinical functioning. Pts received IT T via an intraventricular Ommaya reservoir. Phase I dosing started at 10 mg, then increasing by 20 mg up to 80mg. Each cycle (C) was 4 weeks with 2x/week treatment in C1, weekly in C2, and every two weeks after C2. Pts were allowed to continue on hormonal agents if systemic disease was controlled at LM development. Concurrent radiation therapy was not allowed, with the exception of localized treatment for pain control. 34 pts were enrolled with 26 in phase 2. The median age was 51 (25–69). IT T was well tolerated with no DLTs seen throughout; determined MTD was 80 mg for phase 2. All pts treated in phase 2 had Her2+ breast cancer, 2 pts in the phase 1 had non-breast histologies. Median cycles completed was 2 (1–22). Median follow up was 9.1 months (0.4–28.9). In phase 2, 5 pts (19.2%) had PR, 13 (50%) had stable disease (SD) and 8 (30.8%) had progressive disease. For phase 2 pts, median PFS pts was 2.4 months (CI 1.0–5.5) and median OS was 12.1 months (CI 4.3–19.6). IT T was tolerated up to a dose of 80mg. Primary endpoint (25% RR) was not met, however 69% of pts showed clinical benefit (SD or better); median OS exceeded historical controls. Future studies are warranted to evaluate IT T in HER2+ LM.